kreasi Alama KREASI ALAM: WORKSHOP POCH BAG ECOPRINT SEBAGAI EDUKASI LINGKUNGAN BAGI SISWA SD AIR TENANG: Ecoprint, Edukasi Lingkungan, Pouch Bag, Siswa SD, Workshop - Novysa Basri; Novianti Novianti; Annisa Nabila; Putri Ariska; Afkar Afkar; Rahmi Hayati; Wahyudi Wahyudi (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2026)
Environmental issues stemming from textile waste and the use of synthetic dyes are on the rise, creating a need for eco-friendly alternatives in fabric production. Ecoprinting—a technique for printing natural patterns using plant materials—offers a solution that also serves as a medium for environmental education for elementary school students. However, its application at the elementary school level remains limited. Therefore, this community service initiative, conducted through a workshop, aims to introduce students at SD Air Tenang to ecoprinting and train them in creating ecoprinted pouches, thereby fostering early environmental awareness. The program employed a combination of awareness-raising and hands-on training. Activities began with an explanation of basic ecoprinting concepts, followed by a demonstration of the "pounding" technique and practical sessions where students printed natural patterns onto fabric to create pouches. Additionally, an interactive discussion regarding the sustainable use of natural resources was held. The results indicate that the students successfully grasped the ecoprinting concept and effectively applied the pounding technique. They also gained a greater appreciation for environmental preservation by utilizing natural materials for fabric coloring. Thus, this workshop contributed to enhancing creative skills while instilling ecological awareness from an early age